Implementasi Nilai-Nilai Pendidikan Islam dalam Mengatasi Dekadensi Moral pada Generasi Z - Aida Imtihana; Fatah Hidayat; Faisal, Faisal (STIKes Ibnu Sina Ajibarang, 2025)
This study relates to the implementation of Islamic educational values in addressing moral decadence among Generation Z. This type of research is a literature review study, with sources of information obtained through the analysis of literature relevant to the subject being discussed, including books, journal articles, research findings, and other related sources. Data analysis in this study involves several stages: identifying the problem, collecting literature, filtering the literature, followed by data tabulation and analysis. Based on the findings and discussion, Islamic education serves as an institution that facilitates the comprehensive development of individuals based on Islamic teachings. The values of Islamic education are crucial in shaping character and personality in accordance with religious principles. Moral decadence among Generation Z refers to the decline of ethical values and deviant behaviors from prevailing social norms. This phenomenon is of serious concern amidst the rapid development of technology and globalization that influence the mindset and behavior of the younger generation. The family plays a vital role in shaping the Islamic character of young people. As the primary environment where individuals first acquire an understanding of moral and spiritual values in Islam, the family bears a great responsibility in teaching and practicing Islamic teachings holistically to all its members, especially the youth. Young people need guidance and role models who can serve as examples, particularly as they enter adolescence. Therefore, education and moral guidance play a crucial role in shaping children's character and in fostering them to become morally upright and responsible members of society.